2020
DOI: 10.1111/ijac.13596
|View full text |Cite
|
Sign up to set email alerts
|

Nano‐hydroxyapatite and nano‐hydroxyapatite/zinc oxide scaffold for bone tissue engineering application

Abstract: Bioceramics have been widely used in medicine and dentistry. One remarkable success of bioceramics is the emergence and clinical use of bioactive ceramics. 1 Over the past 20 years, a wide range of calcium phosphates-such as hydroxyapatite (HA), 2-4 amorphous calcium phosphate, 5-8 tetra-calcium phosphate, 9 and mono-di calcium phosphate 10-12-has been studied in both dentistry and in orthopedics fields. Micro or nanoscale HA have been investigated, and their mechanical properties have been tested. 13 Calcium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The behavior of crack propagation and its rate in Ecoflex elastomers is distinct from that of other solid materials such as fiber-reinforced polymers [ 23 , 24 , 25 , 26 , 27 , 28 ] and other materials [ 29 , 30 ]. In most cases mentioned earlier, crack initiation begins from the designated notch position and travels parallel to it.…”
Section: Methodsmentioning
confidence: 99%
“…The behavior of crack propagation and its rate in Ecoflex elastomers is distinct from that of other solid materials such as fiber-reinforced polymers [ 23 , 24 , 25 , 26 , 27 , 28 ] and other materials [ 29 , 30 ]. In most cases mentioned earlier, crack initiation begins from the designated notch position and travels parallel to it.…”
Section: Methodsmentioning
confidence: 99%
“…The nano-hydroxyapatite/ZnO and PCL/ZnO showed bone tissue regeneration. 215 These scaffolds showed excellent and greater biocompatibility and biomineralization provided with the nano-porous matrix for the attachment and proliferation of cells.…”
Section: Mechanisms and Various Biomedical Applications Of Zno Thin F...mentioning
confidence: 99%
“…It was confidently expected that this exploration would advance tissue culture technology by increasing the rate of plant in vitro regeneration in various species. Heidari et al [ 209 ] and Harikrishnan and Sivasamy [ 210 ] reported the efficacy of nanohydroxyapatite/ZnO (HA/ZnO) scaffolds and polycaprolactone/ZnO(PCL-ZnO) scaffolds for bone tissue regeneration in human osteoblast cells. Improved biocompatibility and biosorption properties were demonstrated by the HA/ZnO scaffold, whereas PCL/ZnO scaffolds offer a nano-porous matrix for improved cell adherence and higher cell proliferation.…”
Section: Application Of Znonps In Tissue Engineeringmentioning
confidence: 99%